Influence of Zn on the distribution and composition of heterogeneous solute-rich features in peak aged Al-Mg-Si-Cu alloys. (15th January 2019) - Guo, M.X.; Li, G.J.; Zhang, Y.D.; Sha, G.; Zhang, J.S.; Zhuang, L.Z.; Lavernia, E.J.
Abstract: The distribution and composition of solute-rich features in peak aged Al-Mg-Si-Cu-(Zn) alloys was investigated via three-dimensional atom probe (3DAP) analysis. Our results show that a heterogeneous microstructure can be readily attained via Zn additions with concomitant improvement in the strength, elongation and strain hardening of peak aged alloy. Moreover, Zn partitioning into solute-rich features with a higher Mg/Si ratio (2.46–2.81) and higher number density were observed in the Zn-containing alloy and attributed to strong interactions among Mg, Si, Cu and Zn atoms. The formation of heterogeneous microstructure in the Zn-containing alloy was rationalized due to an increased tendency for clustering. Graphical abstract: Unlabelled Image